Toward Cleaner Industries: Smart Cities’ Impact on Predictive Air Quality Management - Kalyan Chatterjee; Muntha Raju; Machakanti Navya Thara; Mandadi Sriya Reddy; M. Priyadharshini; N. Selvamuthukumaran; Saurav Mallik; Haya Mesfer Alshahrani; Mohamed Abbas; Ben Othman Soufiene (IEEE Access, 2024)
The Smart City (SC) framework has garnered global recognition for its transformative influence on society through innovative solutions. However, the extensive use of Internet of Things (IoT) devices in SCs raises concerns regarding electronic waste and resource consumption. Addressing this challenge necessitates integrating smart grid systems to safeguard SC residents’ environment and well-being. Accurate air quality prediction is essential for informed societal decisions, safe transportation, and disaster preparedness. This study introduces a novel approach: Towards Cleaner Industries: Smart Cities’ Impact on Predictive Air Quality Management (SPAM). The SPAM model utilizes a bidirectional stacking mechanism of long short-term memory neural networks, considering spatiotemporal correlations to forecast future air pollutant concentrations. Surpassing conventional methods, SPAM model enhances accuracy while reducing computational complexity. Experimental findings demonstrate enhanced efficiency and accuracy, underscoring its practicality in industrial contexts. The SPAM model represents a significant advancement in promoting environmental sustainability within the SC framework.